Effect of temperature on the dielectric properties of 0-3 PZT-cement composites - A. Chaipanich (2018)
In this work, 0-3 lead zirconate titanate (PZT) was mixed with normal Portland cement to produce 0-3 connectivity composites. The effect of temperature on the dielectric properties such as the dielectric constant and dielectric loss was determined. It was found that with increasing PZT content the Tcincreases where the optimum dielectric constant was observed and that at the temperature up to 100°C there is a significant change in the dielectric properties in PZT-cement composites. This is due to the loss of water molecules at up to 100°C. At above 100°C, the dielectric properties of the composites were found to have a similar behavior to that of PZT ceramic with Tc being ≈420°C.